Inter‐Annual Variability of the Along‐Shore Lagrangian Transport Success in the Southern Benguela Current Upwelling System. Issue 3 (9th March 2022) - Ragoasha, Moagabo Natalie; Herbette, Steven; Veitch, Jennifer; Cambon, Gildas; Reason, Chris J. C.; Roy, Claude
Abstract: A 3‐km resolution regional ocean model is used to investigate the role of wind‐driven coastal circulation and mesoscale variability on the inter‐annual variability of transport success in the southern Benguela between Cape Point (34°S) and St Helena Bay (32°S) from 1992 to 2011. Lagrangian particles are released within the top 100 m of the water column along an across‐shore transect off Cape Point. Transport success is given by the ratio of the number of particles that reach St Helena Bay over the total number of particles released. The analysis of transport success anomalies and their relationship with the local circulation and wind forcing reveal that there is no single driver of the inter‐annual variability. The transport success variability of particles released on the shelf (depths <300 m) mainly depends on their capacity to remain embedded within the coastal Benguela Jet. Nevertheless, peaks in offshore Ekman transport and episodic occurrence of a poleward inner‐shelf counter‐current contribute to negative anomalies. For particles released on the outer shelf edge (depths >500 m), across‐shore transports induced by mesoscale eddies are the main contributors to transport success variability. Rare passage of Agulhas rings near the shelf edge can induce strong offshore advection of particles into the open ocean. In contrast, shelf‐edge cyclonic eddies favor the onshore transport of particles originating from the outer shelf edge and thus contribute to increasing transport success. Plain Language Summary: This study investigates the inter‐annual variation of Lagrangian transport in the southern Benguela Current upwelling system using a high‐resolution regional ocean model and particle tracking experiments. Transport of fish eggs and larvae by upper ocean currents is crucial for the marine ecosystem in this highly productive region since the spawning and nursery areas used by anchovies are separated by large distances (∼400 km). The alongshore connectivity between the Cape Peninsula and St Helena Bay from 1992 to 2011 is analyzed and linked to the regional ocean circulation and wind‐forcing on an inter‐annual time scale. We find that transport success is influenced by several drivers including the Benguela Jet, Ekman transport, the coastal inner‐shelf poleward counter‐current, and occasional interactions with eddies such as Agulhas rings and shelf‐edge cyclonic eddies. These findings provide a valuable information for future studies on the role of the physical drivers that impact the transport of larvae and eggs in the southern Benguela, underlining that no single driver can account solely for extreme positive or negative events in transport success. Key Points: There are multiple physical drivers of the interannual variability of along‐shore transport success in the southern Benguela upwelling Positive anomalies of transport success are associated with a strong Benguela Jet, reduced offshore and southward transport Negative anomalies are associated with enhanced offshore and southward particles transport, and anticyclonic eddies